Das kulturelle Erbe von Arzach (Universitätsverlag Kiel | Kiel University Publishing, 2024)
The Artsakh/Nagorno-Karabakh region is populated mostly by ethnic Armenians. Cultural traces from over two millennia indicate their long history on site. Due to the armed conflict with Azerbaijan and the violent takeover of the Republic of Artsakh by the Azerbaijani government on September 20, 2023, these cultural assets are currently at massive risk. This volume documents an interdisciplinary conference that took place in Armenia in 2022. It offers the most complete trilingual overview to date on the history, culture and global contacts of this unshielded area in the Southern Caucasus.